(untitled) (Biological Sciences - PJSIR, 2000)
Synthesis of MMA-Co-BA was accomplished at 60"C using benzoyl peroxide as initiator. It is observed that MMA and BA form copolymers in all monomeric ratios. Tensile properties and hardness were determined for the films prepared from the blends of chlorinated rubber and MMA-Co-BA. Tensile strength of the films increases as the amount of chlorinated rubber is increased. The increase in tensile strength might be due to intermolecular and intramolecular rearrangements of copolymer molecules with chlorinated rubber and an increase in the crosslinking density of the system. The rearrangement of copolymer molecules with chlorinated rubber also enhanced the elongation at break. The addition of copolymer and plasticizer make the films more soft and flexible.